2019
DOI: 10.1002/ijc.32747
|View full text |Cite
|
Sign up to set email alerts
|

Circulating lncRNA SNHG11 as a novel biomarker for early diagnosis and prognosis of colorectal cancer

Abstract: Colorectal cancer (CRC) is the third most common cancer and the second leading cause of cancer mortality worldwide. Emerging evidence indicates that tumour cells release substantial amounts of RNA into the bloodstream, in which RNA strongly resists RNases and is present at sufficient levels for quantitative analyses. Our study aimed to discover blood‐based markers for the early detection of CRC and to ascertain their efficiency in discriminating healthy controls, patients with polyps and adenomas and cancer pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
85
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 141 publications
(93 citation statements)
references
References 40 publications
(68 reference statements)
1
85
0
Order By: Relevance
“…More and more evidence shows that lncRNA is closely related to the occurrence and progress of HCC. 9,10 In our study, LncRNA microarray assay and RT-PCR results showed that SNHG11 had higher expression in HCC tumor tissues compared with normal samples. SNHG11 was also increased in HCC cells than normal cell lines.…”
Section: Discussionsupporting
confidence: 48%
“…More and more evidence shows that lncRNA is closely related to the occurrence and progress of HCC. 9,10 In our study, LncRNA microarray assay and RT-PCR results showed that SNHG11 had higher expression in HCC tumor tissues compared with normal samples. SNHG11 was also increased in HCC cells than normal cell lines.…”
Section: Discussionsupporting
confidence: 48%
“…Therefore, establishing a reliable risk assessment model is urgently needed to assess the survival prognosis of patients with colon cancer and optimize clinical treatment decisions. In recent years, genomic research has greatly enhanced our understanding of the mechanism underlying colon cancer development (Coebergh van den Braak et al, 2018) and revealed the potential value of molecular biomarkers in the diagnosis and evaluation of survival prognosis in patients with colon cancer (Galamb et al, 2019;Xu et al, 2019). Therefore, individualized treatment plans can be tailored to different patients with colon cancer to improve their survival prognosis.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, our expression analysis identified two snoRNA/host gene couples (SNORA71E/SNHG11 and SNORA5C/TBRG4) which are transversally up-regulated in different cancer series, indicating that they may have a role in cellular mechanisms of tumorigenesis. Even though the relevance of these two snoRNAs has not yet been reported, different groups have reported alterations in SNHG11 and TBRG4 in different cancer types [77][78][79][80][81].…”
Section: Discussionmentioning
confidence: 99%